PENGARUH SELF DIRECTED LERANING DAN KEDISIPLINAN SISWA TERHADAP HASIL BELAJAR BAHASA INGGRIS KELAS VIII SMP NEGERI I SUNGAI LALA KABUPATEN INDRAGIRI HULU - Eton Eton; Jesi Alexander Alim; Lidwina Sri Ardiasih (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2023)
This study aims to find out the influence of student learning independence and discipline on the results of learning English class VIII SMP Negeri 1 Sungai Lala Kabupaten Indragiri Hulu. This research used a quantitative approach of associative type of research. The data analysis technique used multiple linear analysis. The results of the study obtained a calculated F value of 67,673 > Ftabel of 3,099 and the result of a Sig. value is 0.000 < 0.05, it can be concluded that there is a significant influence between Student Independence (X1) and Learning Discipline (X2) on English Learning Outcomes of Class VIII Students of SMP Negeri 1 Sungai Lala, Indragiri Hulu Regency (Y). Based on the results of the coefficient of determination, the result of R Square was 60.3%. This shows that the two free variables consisting of Student Independence and Learning Discipline contributed to influencing student English learning outcomes by 60.37%. Based on this, it is concluded that the better the Student Independence and Learning Discipline, the better the English Learning Outcomes of Class VIII Students of SMP Negeri 1 Sungai Lala, Indragiri Hulu Regency.